Closure to discussion of “Procedure for assessing the liquefaction vulnerability of tailings dams” by Ledesma, O, Sfriso, A, and Manzanal, D - Ledesma, Osvaldo Nicolas (2023)
The authors thank the discussers for their comments (Reid et al., 2023), which are mostly related to addressing key uncertainties when completing the analysis proposed by the authors in their work (Ledesma et al., 2022), and to the response of the Modified Pastor-Zienkiewicz (MPZ) constitutive model (Manzanal et al., 2011) employed in the same work.The authors believe that recognizing and dealing with uncertainties, such as the ones highlighted by the discussers, will provide additional insights for assessing the liquefaction vulnerability of tailings dam systems (Ledesma et al., 2022) using readily available deformation modelling tools.The authors would also like to highlight that the proposed procedure for assessing liquefaction vulnerability is not a triggering analysis. The proposed actions are not intended to be relevant or realistic for a given dam. However, they should be understood as numerical excursions around a stable configuration to check the stability of such equilibrium. Also, the proposed procedure could be completed using constitutive models other than MPZ. However, there are some key characteristics that the selected constitutive model should have and are described in more detail in Ledesma et al. (2022).